Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5771/0949-6181-2019-2-259
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived top management involvement and knowledge sharing affect perceived project performance? Evidence from the banking sector

Abstract: This study explores the impact of perceived top management involvement and knowledge sharing on perceived project performance. Relationships are examined from a sample of CEOs, directors and project managers from one large international bank in Serbia. Our results confirm that the “human factor” is critical to project success because perceived top management commitment exerts the most relevant direct relation, in addition to having an indirect relation through perceived knowledge management. Moreover, a nontri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results offer important insight and contribution in the local context, where many banks organize their work through teams, but there is not enough information yet on how to create effective teams and increase their performances. To date, many researchers investigated topics such as the satisfaction and loyalty of the employees in the banking sector [53,54], leadership [55] and top management involvement and knowledge sharing [56,57], and change management and sustainability [58]. Therefore, the results of this paper can serve as a starting point for creating strategies and actions for team development and training with the aim of reaching higher level of team members' effectiveness and performances.…”
Section: Discussionmentioning
confidence: 99%
“…The results offer important insight and contribution in the local context, where many banks organize their work through teams, but there is not enough information yet on how to create effective teams and increase their performances. To date, many researchers investigated topics such as the satisfaction and loyalty of the employees in the banking sector [53,54], leadership [55] and top management involvement and knowledge sharing [56,57], and change management and sustainability [58]. Therefore, the results of this paper can serve as a starting point for creating strategies and actions for team development and training with the aim of reaching higher level of team members' effectiveness and performances.…”
Section: Discussionmentioning
confidence: 99%
“…The intensive use of knowledge management technologies in the banking sector is another reason to choose the sample from this sector. In literature, it is observed that there are some studies (Abbas et al, 2013;Abuazoum and Azizan 2013;Bilal, 2019;Milošević et al, 2019) on knowledge sharing in the banking sector. Knowledge is considered as an important asset and knowledge sharing among employees is considered as vital in banking sector (Kridan and Goulding 2006, p.216).…”
Section: Introductionmentioning
confidence: 99%